GbCYP72A1 Improves Resistance to Verticillium Wilt via Multiple Signaling Pathways - Xu, Jianwen (Plant disease, 2023)
Verticillium dahliae is a fungal pathogen that causes Verticillium wilt (VW), which seriously reduces the yield of cotton owing to biological stress. The mechanism underlying the resistance of cotton to VW is highly complex, and the resistance breeding of cotton is consequently limited by the lack of in-depth research. Using quantitative trait loci (QTL) mapping, we previously identified a novel cytochrome P450 (CYP) gene on chromosome D4 of Gossypium barbadense that is associated with resistance to the nondefoliated strain of V. dahliae. In this study, the CYP gene on chromosome D4 was cloned together with its homologous gene on chromosome A4 and were denoted as GbCYP72A1d and GbCYP72A1a, respectively, according to their genomic location and protein subfamily classification. The two GbCYP72A1 genes were induced by V. dahliae and phytohormone treatment, and the findings revealed that the VW resistance of the lines with silenced GbCYP72A1 genes decreased significantly. Transcriptome sequencing and pathway enrichment analyses revealed that the GbCYP72A1 genes primarily affected disease resistance via the plant hormone signal transduction, plant-pathogen interaction, and mitogen-activated protein kinase (MAPK) signaling pathways. Interestingly, the findings revealed that although GbCYP72A1d and GbCYP72A1a had high sequence similarity and both genes enhanced the disease resistance of transgenic Arabidopsis, there was a difference between their disease resistance abilities. Protein structure analysis revealed that this difference was potentially attributed to the presence of a synaptic structure in the GbCYP72A1d protein. Altogether, the findings suggested that the GbCYP72A1 genes play an important role in plant response and resistance to VW